Contracts with protection duties. A propos of Constitutional and Civil Law connection - Morales Hervias, Rómulo (2013)
This essay examines protection duties arising under a contract. Its doctrinal and comparative case-law development is very broad. In Peru, national doctrine has studied it from case-law specific cases. The purpose ofthis study is to develop the analysis of autonomy of these duties towards main and secondary obligations arose under contracts in order to give legal bases not only from Civil Law but also from Constitutional Law perspective.